Coccidioidomycosis with cutaneous manifestation of erythema nodosum in Taiwan - Chien-Ming Chen; Hua-En Lee; Shu-Ying Li (Wolters Kluwer Medknow Publications, 2010)
Coccidioidomycosis is a fungal disease endemic to the southwestern USA, northern Mexico, and focal areas in Central and South America, but it is rarely reported in Taiwan. We report a case of coccidioidomycosis of probable pulmonary origin in a young woman, who came back to Taiwan after a 10-month stay in the Central Valley of California. Coccidioidomycosis was suspected by typical constellation of symptoms and signs of Valley fever and subsequent desert rheumatism. The diagnosis was confirmed by positive results of latex agglutination, immunodiffusion tube precipitation and immunodiffusion complement fixation tests. We prescribed symptomatic treatment without any anti-fungal agent according to the Infectious Disease Society of America guidelines, and the clinical symptoms and signs gradually subsided 3 weeks later. Although coccidioidomycosis is rare in Taiwan, it is believed that the real incidence has been underestimated. Clinicians must be familiar with the typical manifestations and consider the diagnosis of coccidioidomycosis when an individual presents with fever, cough, arthralgia and skin eruptions such as erythema nodosum and/or erythema multiforme with a traveling history to the endemic area.